Culture, Geographies or Accounting Regimes: Which are Drivers for Risk-taking in European and Asian Banks? - Lopes, A.I. (Proceedings of the 15th Eurasia Business and Economics Society Conference, 2015)
Our goal in this paper is achieved using the Hofstede’s model of cultural dimensions that has become an internationally recognized standard. A sample covering 41 countries from Europe and Asia and about 3,150 bank-years observations was selected to represent low and high averse to risk characteristics. The research is conducted to investigate the influence of culture attributes of risk-taking on the reporting of some variables related to risk, identifying whether or not geographies or accounting regimes are also determinants. We use two proxies for risk-taking. First, we focus on Provisions for Loan Losses as an estimative of incurred loan losses. The Provisions for Loan Losses reflect management´s estimate of the incurred loan losses that must be recognized on the profit or loss statement. Since these estimates measure fluctuations in the recognized credit losses during the period, we want to identify the effect of national cultural on loan losses provisions. Second, we focus on risk-weighted assets as an estimative for unexpected losses. Risk weighed assets calculated by individual banks’ internal models can be significantly different for similar risks ((HLEG, 2012) and they leave room for individual banks to “optimize” capital requirements by underestimating their risks and thus being permitted to hold lower capital (Das and Sy, 2012). Our research is designed using a twofold perspective. First of all, we examine if the distribution of our proxies for risk taking are different between independent groups. We compare the outcomes based on groups clustered by national culture dimensions, geographies and accounting regimes. Secondly, we examine if culture is a determinant of banks that present higher or lower amounts of incurred and unexpected losses. We use a binary logistic model to test the probability of countries with lower (higher) risk-taking behavior report higher (lower) provisions for loan losses and disclose lower (higher) percentages of risk weighed assets. Our findings suggest that national culture is (is not) a determinant for the probability of reporting higher or lower level of loans loss provisions (risk weighed assets). These findings are consistent for banks in different geographies (Europe vs Asia) and subject to different accounting regimes (IFRS vs local standards).